An analysis of prescriptions for coronary heart disease with comorbid conditions in health care institutions of Ukraine - N. A. Bilousova; M. M. Dolzhenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2025)
Coronary heart disease (CHD) remains the leading cause of mortality among non-communicable diseases in Ukraine and is often accompanied by various comorbid conditions. Providing pharmaceutical care to patients with CHD and comorbid conditions requires a comprehensive approach that includes ensuring access to medications, supervising rational pharmacotherapy in accordance with domestic and international clinical guidelines, monitoring trends in medication consumption, optimizing the supply of medicines, and developing standards for pharmaceutical care during martial law and the post-war period.